Fund performance of Amanah Saham Nasional 2 (ASN2) based on annualized return and its benchmark / Mohd Saharazad Sabran - Sabran, Mohd Saharazad (Faculty of Business and Management, 2010)
This case study focuses on measuring the performances of fund for Amanah Saham Nasional 2 (ASN 2) scheme towards benchmark provided by Bursa Malaysia. The aim is to increase the total return and average total return of the fund beyond the benchmark provided. The study includes the timely total return for the period 2005,2006,2007,2008 AND 2009. Moreover, the study is vital to highlight what are the factors that can affect the performance of fund for ASN 2 towards benchmark provided by Bursa Malaysia. It has also been observed that high-quality Credit Risk Management staffs are critical to ensure that the depth of knowledge and judgment needed is always available, thus successfully managing the credit risk.